Compilation of Criteria for Types of Data Collection in Management of Research Methods - Aini, Qurotul; Zaharuddin, Zaharuddin; Yuliana, Yuliana (Pandawan, 2018)
Writing activities are an integral part of the learning process. Writing means managing ideas systematically and expressing them explicitly. Writing can mean lowering or describing graphic symbols that describe a language understood by someone. For a researcher, compiling a research management is a very important step because this step greatly determines the success or failure of all research activities. Research activities are one of the activities that are scientific in nature. Before someone starts with research activities then he must make a written plan commonly referred to as the management of research data collection. In addition, scientific research management has a clear purpose, which can later be useful as a study material about a matter and most importantly as a reference in making decisions both for the benefit of the public or government or the private sector or company.